2013
DOI: 10.4028/www.scientific.net/amm.446-447.738
|View full text |Cite
|
Sign up to set email alerts
|

Design, Modeling and Finite Element Static Analysis of a New Two Axis Solar Tracker Using SolidWorks/COSMOSWorks

Abstract: This paper presents the now design, modeling and static analysis of a new two-axis solar tracker (Azimuth and Altitude). The tracker is an electro-hydraulic device that keeps photovoltaic panels in an optimum position perpendicularly to the solar radiation during daylight hours. The tracker of 24 m² panel’s size was designed using the SolidWorks 3D CAD software. The finite element method (FEM) is adopted to ensure the stability and the reliability of the tracker. COSMOSWorks was used to determine displacement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Now, following the guidelines proposed by the mechatronic design methodology, the simulation of static loads was performed to verify that each proposed mechanism did not suffer tension failures when applying a force, as shown in Table 3 . For this purpose, the SolidWorks Simulation software was used, which estimates the Von Mises stress, a scalar that can indicate a good design for ductile materials, such as those used in [ 28 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Now, following the guidelines proposed by the mechatronic design methodology, the simulation of static loads was performed to verify that each proposed mechanism did not suffer tension failures when applying a force, as shown in Table 3 . For this purpose, the SolidWorks Simulation software was used, which estimates the Von Mises stress, a scalar that can indicate a good design for ductile materials, such as those used in [ 28 ].…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Despite the advanced levels this technology has achieved recently, the efficiency and high initial investment costs required remain a considerable challenge for investors, researchers, and other stakeholders in this technology. In the last decade, the use of single and dual-axis tracking systems has played an important role in terms of gaining high amounts of energy, and much research has been conducted to analyse and design various types of solar trackers [1][2][3][4][5]. These studies found that the selfweight of the structure, and wind loads, are the primary forces that affect its stability directly, and hence such structures should be designed and tested to a high level.…”
Section: Introductionmentioning
confidence: 99%
“…Static analyses are performed to give information about the ability of the structure to withstand the extreme design loads, structural properties and strains. All these information let to know the strength, stiffness and stability of the structure [4,5].…”
Section: Introductionmentioning
confidence: 99%